The effect of endosperm vitreousness on fermentation characteristics and in vitro digestibility of maize - Burden, Petro Trudene (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2010.